Review of Arruzza, C. A Wolf in the City: Tyranny and the Tyrant in Plato’s Republic (2019) - Maia, Rosane de Almeida (Revista Archai, 2020)
Review of Arruzza, C. A Wolf in the City: Tyranny and the Tyrant in Plato’s Republic (2019).